Effective Coughing Exercises and Aromatherapy Can Clean The Air Tracts in Pulmonary TB Patients : a Case Study - Amanda Hafidz Mardana (Health Gate, 2026)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease caused by Mycobacterium Tuberculosis. Pulmonary TB can also cause secretion retention due to increased mucus production by epithelial cells of the lungs. Pulmonary TB This study aims to determine the effectiveness of effective coughing ability in pulmonary TB patients. The case study design in 4 patients used a multiple case study, namely studying in depth several patients with the same case, the case study was carried out by identifying patients, conducting patient assessments, conducting planning, determining diagnoses, and providing implementation and evaluation. After 3 days of intervention, there was a decrease in sputum production in the four patients, indicating that the intervention given was effective in helping clear the patient's airway.